Enhancing Diagnostic Accuracy in Oral Radiology: A Case for the Basic Sciences - Baghdady, Mariam (2013)
Background: Cognitive processing in diagnostic oral radiology requires a solid foundation in the basic sciences as well as knowledge of the radiologic changes associated with disease. Although it is generally assumed that in dentistry, students must acquire both knowledge sets, little is known about the role or impact of the basic sciences on clinical reasoning because the two have traditionally been taught separately in the curriculum. Objectives: This dissertation investigates the role of basic sciences in oral radiology and its effects on diagnostic accuracy. The studies were designed to satisfy the following research aims: 1) to examine and compare the effects of integration and segregation of the basic and clinical sciences on diagnostic accuracy; 2) to examine the effects of basic science instructional methodology and diagnostic strategy on diagnostic outcomes; 3) to explore the potential interactions between instructional methodologies used to teach disease categorization and diagnostic strategies; and 4) to examine the effects of testing the basic sciences on diagnostic accuracy in an integrated instructional methodology. Methods: We conducted three quantitative studies, all of which involved a learning phase and an immediate testing phase that assessed diagnostic performance and memory. In each of the studies, learning strategies, and or testing frequency were varied. We also included performance assessment of diagnostic ability and memory, one week after the initial learning phase. Results: Our results show that students who learned basic sciences explanations had higher diagnostic accuracy when using a holistic System 1 type diagnostic strategy than those who did not. We also demonstrated that basic science knowledge was the most effective when directly integrated with the clinical sciences, and this result is further enhanced with testing. Conclusions: We conclude that integrated basic science learning provides a coherent framework that has the potential to significantly improve the diagnostic accuracy of training dentists.